Memoirs of the Court of George III
1 online resource (1664 pages).
Keywords: "Memoirs of the Court of George III presents annotated and indexed editions of four works whose authors associated with the court in different ways. Charlotte Papendiek and several members of her family were servants of the royal household. Mary Delany and Lucy Kennedy, although not employed by the court, lived in Windsor in 'grace and favour' accommodation provided by the king and had frequent contact there with the royal family and the court. Queen Charlotte was at the centre of court life and controlled her own establishment within the royal household."--Page xv.